Comportamento infantil durante consultas odontológicas sequenciais : influência de características clínicas, psicossociais e maternas - Cademartori, Mariana Gonzalez (2014)
One of the most challenging aspects faced by pediatric dentists is behavior management. Child behavior in the dental setting is a multifactorial phenomenon and studies have suggested that some factors may predict children s behavior in dental settings. Thus, this dissertation aimed to assess the behavior of children during sequential dental visits according to the treatment the child received, as well as to investigate the factors that can influence the behavior of children during dental treatment. A convenience sample of children aged from 7-to-13 years old attending a Pediatric Dentistry Clinic was accompanied during 4 sequential visits. Behavior was classified according to Frankl s scale. Mothers and children were interviewed previously to the 1st visit to collect information on demographic, socioeconomic and psychosocial characteristics. The complexity of treatment in each visit was classified as minimally invasive, invasive or very invasive. Behavior trajectory following the visits was assessed. To test the association of the independent variables and behavior Chi-squared and Fisher s exact tests were used. To determine the effect of the variables on the outcome behavior, crude and adjusted Poisson regression analyses were used (Relative Risk; 95% Confidence Interval). The level of significance was set at 5%. A total of 111 mother-child dyads were included. The behavior at the first visit was 100% positive for all children. In the trajectory of behavior during the sequential visits, the majority of children (over 55%) showed positive behavior. Negative behavior was influenced by complexity of treatment, dental pain, dental fear and maternal education, after adjustments. Anesthesia, extraction of primary teeth, use of rubber dam and endodontics were the procedures associated with negative behavior. Dental fear may be considered a predictor of child behavior, evidencing that besides the treatment procedure, maternal and children characteristics should also be considered by the dentist to predict and better manage behavior